2017
DOI: 10.1002/cbm.2029
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and associated factors among young offenders in Chile: a cross‐sectional study

Abstract: Our findings suggest that greater efforts must be made to identify vulnerable young people much earlier. Few of these young offenders with mental health problems had been well adjusted in health, education or socially before this period of detention. © 2017 The Authors. Criminal Behaviour and Mental Health Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
8
1
1
Order By: Relevance
“…As we have pointed out, insult and stressors derived by neglect and abuse at early life may lead to long-term consequences in youngsters (Gunnar and Donzella, 2002 ). The extremely stressful environment experienced by young offenders may be related to high incidence of mental disorders, as recently reported by Gaete et al ( 2017 ). However, no investigation has addressed the link between epigenetic mechanisms and psychological consequences for these victimized children.…”
Section: Discussion and Future Developmentsmentioning
confidence: 57%
See 1 more Smart Citation
“…As we have pointed out, insult and stressors derived by neglect and abuse at early life may lead to long-term consequences in youngsters (Gunnar and Donzella, 2002 ). The extremely stressful environment experienced by young offenders may be related to high incidence of mental disorders, as recently reported by Gaete et al ( 2017 ). However, no investigation has addressed the link between epigenetic mechanisms and psychological consequences for these victimized children.…”
Section: Discussion and Future Developmentsmentioning
confidence: 57%
“…In a cross-sectional study of psychological disorders observed in young Chilean offenders, researchers found a prevalence of mental illnesses such as marijuana dependence disorder, major depressive disorder, and anxiety disorders. This investigation found also a connection between these mental disorders and childhood deprivation and maltreatment, and parental death and drug abuse (Gaete et al, 2017 ).…”
Section: Relevance Of Neurobiological Epigenetics In Educationmentioning
confidence: 78%
“…We used the Spanish version of the MINI because of its appropriateness and easy application by psychologists, because it includes the variables of interest in this study (which have been replicated) [31, 32], and because it has been applied to young offenders, for example in Chile [33]. A mental health screening tool should consider important contextual factors in the implementation of screening.…”
Section: Discussionmentioning
confidence: 99%
“…Prisoners are highly vulnerable to a mental disorder as compared to the wider community ( 15 ), a finding supported by a study done in the United Kingdom that found major depressive disorder was 61.7% and of anxiety 53.3% among incarcerated women ( 16 ). In addition, a study of young offenders in Chile found 22% had depression and 24% had an anxiety disorder ( 17 ). One recently conducted study among New Zealand prisoners revealed that nearly a third (32%) had a mood disorder (depression), while 30% had an anxiety disorder ( 18 ).…”
Section: Introductionmentioning
confidence: 99%